Authorship and Audience : Literary Performance in the American Renaissance - Railton, Stephen (Book collections on Project MUSE., 2014)
Stephen Railton's study of the American Renaissance proposes a fresh way of conceiving the writer as a performing artist and the text as an enactment of the drama of its own performance. Railton focuses on how major prose works of the period are preoccupied with their readers--how they seek to negotiate the conflicted space between the authors, who brought to the act of publication their own anxieties of ambition and identity, and the contemporary American reading public, which, as a growing mass audience in a democracy, had acquired an unprecedented authority over the terms of literary per.